Atypical carcinoid of the lung: A case report - Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
A 3D-year old woman came to Dr Sardjito Hospital with chief complain of dyspneu that she had since 1 month before her visit. Clinicalexamination revealed a dull percussion below. The second intercostal of the left chest. The chest X ray revealed massive pleural effusion in the left chest, could not exclude a mass in left lung. Thoracoscopic biopsy of the left lung mass was done. Macroscopic examination of lung tissue sample revealed fragmented tissue, with volumeof 0.25 cc, blackcolour, and rubberyconsistency. The diagnosis of atypicalcarcinoid with small cell carcinoma as a differential diagnosis was determined based on morphological pattern. Immunohistochemical staining examination showed expression of cytokeratin, CAM5.2, and synaptophysin, but showed negative expression of chromogranin, CD56, and TTF-1 .A diagnosis of an atypical carcinoid was confirmed based on the immunohistochemicalexamination. A very rare case of atypical carcinoid of the lung in a non-smoker 3D-yearoldwoman with morphologicaldiagnostic problem solved by immunohistochemical staining was reported.